Dye-sensitized solar cells with inkjet-printed dyes. Issue 7 (21st June 2016) - Hashmi, Syed Ghufran; Özkan, Merve; Halme, Janne; Zakeeruddin, Shaik Mohammed; Paltakari, Jouni; Grätzel, Michael; Lund, Peter D.
Abstract : Inkjet printing dyes on TiO2 films enables the creation of DSSCs with tailored transparency, color density gradients, and patterns of multiple dyes on the same photoelectrode. Abstract : The slow process in which the light absorbing dye molecules are adsorbed from solution on the nanocrystalline TiO2 photoelectrode film has been a handicap to the fast and cost-effective fabrication of dye-sensitized solar cells (DSSCs) using printing techniques. Here, we report a versatile dye sensitization process, achieved by inkjet printing a concentrated dye solution over the TiO2 film, which produces solar cells with equal performance and stability as obtained using the popular dye drop casting method. In addition to allowing precise control of dye loading required for dispensing just the right amount of dye to achieve uniform and full coloration of the TiO2 films without any need for washing off the excess dye, inkjet printing also makes it possible to freely adjust the amount and position of the dye to create DSSCs with tailored transparency, color density gradients, and patterns of one or more dyes on the same electrode. The method was confirmed to be applicable also for non-transparent, high-efficiency DSSC designs that employ a light scattering layer. The inkjet-dyed DSSCs exhibited high stability, retaining almost 100% of their conversion efficiency ( η = 6.4 ± 0.2%) and short circuit current density ( J SC = 14.2 ± 0.6 mA cm −2 ) when subjected to a 1000 h accelerated aging test under 1 Sun illumination at 35 °C, followed by additional 1154 hours under 0.5 Sun at 60 °C. These results overcome one of the main hurdles in realizing fully printed DSSCs and open opportunities for entirely new DSSC designs.